Carotenoids and carotenoid esters of orange- and yellow-fleshed mamey sapote (Pouteria sapota (Jacq.) H.E. Moore & Stearn) fruit and their post-prandial absorption in humans. (15th April 2017) - Chacón-Ordóñez, Tania; Schweiggert, Ralf M.; Bosy-Westphal, Anja; Jiménez, Víctor M.; Carle, Reinhold; Esquivel, Patricia
Highlights: Different mamey sapote genotypes are characterized by their specific carotenoid profiles. Orange-fleshed fruits contained higher amounts of keto-carotenoids. Neoxanthin, violaxanthin, and other epoxides prevailed in yellow-fleshed fruits. Mamey sapote contained potentially vitamin A-active sapotexanthin and cryptocapsin. Post-prandial absorption of sapotexanthin was proven for the first time. Abstract: Although different genotypes of mamey sapote with distinct pulp colors are consumed in countries from Central to South America, in-depth knowledge on genotype-related differences of their carotenoid profile is lacking. Since the fruit was found to contain the potentially vitamin A-active keto-carotenoids sapotexanthin and cryptocapsin, we sought to qualitatively and quantitatively describe the carotenoid profile of different genotypes by HPLC-DAD-MS n . Sapotexanthin and cryptocapsin were present in all genotypes. Keto-carotenoids such as cryptocapsin, capsoneoxanthin, and their esters were most abundant in orange-fleshed fruit, whereas several carotenoid epoxides prevailed in yellow-fleshed fruit. Differing carotenoid profiles were associated with different color hues of the fruit pulp, while the widely variable carotenoid content (3.7–8.0 mg/100 g FW) was mainly reflected by differences in color intensity (chroma C ∗ ). Furthermore, the post-prandial absorption of sapotexanthin to human plasma was proven for the first time. Besides sapotexanthin, cryptocapsin was found to be resorbed.